Comprehensive Review on Manufacturing Process and Characterization of Biosimilar Drugs - Mehmood, Yasir (International Journal of Applied Sciences and Biotechnology, 2018)
According to the World Health Organization, the prevalence of deadly neoplasms and endocrine, blood, and immune disorders will observe an incredible rise in coming decades followed by increased demand of affordable treatments. Keeping this incident in mind, the development of similar drugs is increasing globally. The sanction of such drugs depends on the conformity with international regulations, which starts with physical presentation of similarities that lie in their physiochemical and functional properties in contrast to the relating product. Consecutive clinical studies are done to physically present similar pharmacological behaviour and to curtail the distrust in relation to their safety points and effectiveness. Here we are to present a physical and biological testing of biosimilar and its reference product, by making use of different procedures and approaches, to judge the physicochemical and biological peculiarities with every possible impact it can cause on its pharmacokinetics, pharmacodynamics, and immunogenicity. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 53-62